Broadband refractory plasmonic absorber without refractory metals for solar energy conversion. (24th December 2020) - Wang, Baoqing; Wang, Wenhao; Ashalley, Eric; Zhang, Xutao; Yu, Peng; Xu, Hongxing; Wang, Zhiming M
Abstract: Electromagnetic wave absorbers with full-spectrum near-unity solar absorption are extremely desirable for solar energy conversion. Here, we theoretically proposed a broadband refractory plasmonic absorber without refractory metal, which has nearly perfect absorption over the whole solar spectrum. The absorber is supported by a periodic refractory dielectric framework of alumina and exhibits superior solar-selective and omnidirectional absorption. The simulated average absorption efficiency is up to 96% from 300 to 1400 nm, and the solar energy absorption efficiency can reach up to 90.8% over the entire solar spectrum range. Moreover, the steady-state temperature profile indicates that the absorber heats uniformly. The broadband refractory plasmonic absorber paves the way for the selective thermal absorption under high-temperature environment and holds great promise for solar energy harvesting and desalination applications.